A STUDY OF THE LEGAL ENVIRONMENT AND IMPLEMENTATION OF CYBERSECURITY IN MONGOLIA'S EDUCATION SECTOR - Munkhtsetseg Erdenebulgan; Munkhjargal Bayanjargal; Byambadorj Dondogmegd (International Journal of Innovative Technologies in Social Science, 2025)
Cybersecurity in the education sector is distinct from other sectors, as the primary participants are children and young people who may not fully comprehend cyber threats and risks. Therefore, it is crucial to devise a strategy to mitigate cyber threats and enhance the cybersecurity knowledge and skills of teachers and staff. The aim of the research is to pinpoint the key challenges, opportunities, and future trends in implementing cybersecurity policies and regulations in Mongolia's education sector. This is essential for minimizing risks.Mongolia's cybersecurity efforts are governed by the 2021 Law on Personal Data Protection and the 2021 Law on Cybersecurity, which establish a system, principles, and legal framework for cybersecurity operations. The legal environment has been in development for years. A study of the legal environment and implementation of cybersecurity in Mongolia's education sector would likely examine how these laws are applied within educational institutions, assess the effectiveness of the current legal framework in protecting data and systems, and identify any challenges in implementing cybersecurity measures in the education sector.